Effect of Polyester and Vinylester Resin Blends on the Physical and Mechanical Properties of Reinforced Composites Coconut Coir Fiber - Muhammad Restu Muhammad Restu; Rahmat Fajrul (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to determine the effect of polyester and vinylester resin blends on the physical and mechanical properties of coconut coir fiber-reinforced composites. Coconut coir fiber was selected due to its abundant availability, although its utilization remains limited. Composites were fabricated using the hand lay-up method with a matrix blend of 70% polyester resin and 30% vinylester resin, with fiber volume fractions of 0%, 5%, 10%, 15%, and 25% (PV0–PV25). Mechanical testing was conducted using a Universal Testing Machine referring to the ASTM D638 standard, while fracture morphology was characterized using Scanning Electron Microscopy (SEM). The results showed that the PV0 specimen exhibited the highest mechanical properties, with a Tensile Strength of 32.30 MPa, Yield Strength of 26.95 MPa, Elongation at Yield of 2.28%, and Tensile Stress at Break of 11.95 MPa. The addition of coconut coir fiber instead reduced the composite's mechanical properties, supported by SEM results revealing fiber pull-out and void formation in the fiber-reinforced specimens. These findings indicate that the quality of fiber-matrix interfacial bonding and the minimization of microdefects play a more critical role in determining mechanical performance than the fiber volume fraction itself.